Pengaruh Komunikasi Dan Pendelegasian Wewenang Terhadap Kinerja Pegawai Pada Kantor Kesyahbandaran Dan Otoritas Pelabuhan Kelas IV Sibolga - Sriayu Putri Lestari; Mhd. Shafwan Koto; Heriyawan Hutagalung (Universitas Sains dan Teknologi Komputer, 2022)
This study aims to determine whether Communication and Delegation of Authority Affects Employee Performance at The Office of Harbormaster and Port Authority Class IV, Sibolga. The type of research used in this study is a quantitative research methodwith a descriptive approach. The sample in this study were employees at the Class IV Sibolga Harbor Authority and Port Authority with the distribution of questionnaires totaling 55 (fifty five) respondents. From the results of the t-test in the study, it is known that the t-count value of Communication is 2.877 and the delegation of authority is 4.193 > t-table 2.00665, while with a significant communication 0.006<0.05, and with a significant delegation of authority 0.000 <0.05, the hypothesis is proposed Communication and Delegation of authority partially or individually have a positive and significant effect on the performance of employees at The Office Of Harbormaster and Port Authority Class IV Sibolga can be accepted. Meanwhile, from the results of the F test, it is known that the calculated F value is 37,176 > F table 3.18 and the significance F count is 0.000 < 0.05 so that the hypothesis proposed by Communication and Delegation of Authority has a positive and significant effect simultaneously or simultaneously on employee performance at The Office Of Harbormaster And Port Authority Class IV Sibolga is acceptable.